Analysis Of Working Capital Growth And Profitability During The Covid 19 Pandemic - Adrian, Luthfy Putera Pratama (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
According to experts, the concept of cooperatives is interpreted from Latin, ie.